A “Proof of Concept” Randomized Controlled Trial of a Video Game Requiring Emotional Regulation to Augment Anger Control Training - Ducharme, Peter; Kahn, Jason; Vaudreuil, Carrie; Gusman, Michaela; Waber, Deborah; Ross, Abigail; Rotenberg, Alexander; Rober, Ashley; Kimball, Kara; Peechatka, Alyssa L.; Gonzalez-Heydrich, Joseph (Frontiers in Psychiatry, 2021)
Emotional dysregulation leading to clinically significant anger and aggression is a common and substantial concern for youth and their families. While psychotropic medications and cognitive behavioral therapies can be effective, these modalities suffer from drawbacks such as significant side effects, high rates of attrition, and lack of real-world skill translation. Regulate and Gain Emotional Control (RAGE-Control) is a video game designed as an engaging augment to existing treatments. The game facilitates emotional regulation skill building through practice modulating physiological arousal while completing a challenging inhibitory task. We compared reduction in anger, aggression, oppositionality, and global severity between two treatment conditions: Anger Control Training (ACT) augmented with RAGE-Control and ACT with a sham version of the game, in a pilot double-blind randomized controlled trial. To begin to understand mechanisms of change, we examined heart rate during game play over the course of the study and explored associations between symptom changes and heart rate changes. Forty youth with clinically significant anger dyscontrol (age 10-17) were randomly assigned to 10 sessions of ACT with RAGE-Control or ACT with sham videogame. Both treatments similarly reduced self-reported anger. However, ACT with RAGE-Control led to larger improvements in aggression (CI: -17 to -1.0, ES: 0.55, p=0.015); oppositionality (CI: -9.0 to -7e-6, ES:0.48, p=0.032); and global severity (CI: -1.0 to-5e-6, ES: 0.51, p=0.023) relative to sham. Participants in the RAGE-Control group saw a decrease in median heart rate during game play (β = 1.2, p<0.001). Larger pre to post decreases in heart rate were significantly associated with larger pre to post decreases in aggression and oppositional behaviors. Augmenting ACT with RAGE-Control reduced behavioral expression of anger, but not the experience of angry feelings, as compared to ACT with a sham version of the game. Increased heart rate control, demonstrated by reduction in median heart rate during gameplay, was associated with decreased aggression and oppositional behavior. Together these findings support that augmenting traditional treatment with technology facilitating heart rate control through skill practice translates to enhancements in real-life behavioral change. Therefore, further exploration into engaging skill-focused games such as RAGE-Control is warranted.